Performance analysis of a keyword search system (Journal of University of Babylon for Engineering Sciences, 2018)
Data mining is the process of discovering patterns in a data set by keyword. Keyword search is the most effective way to discover information in documents. But somewhere, sometimes just searching for a keyword is not enough; with research restricting that keyword has become a necessity. Like in social media abuse of word is increasing. Many systems worked on only detecting an inappropriate word; not on restriction of that word. So here in this paper keyword search method is proposed for social media which not only finds the inappropriate words, but also restrict that word from publishing on the media.